Analysis of Inequality of Economic Development in Districts/Cities Region of Former Kedu Residency in Central Java Province - Hisyam Maskanudin; Arif Andri Wibowo (EKO-REGIONAL, 2018)
Differences in the level of economic progress between regions will lead to imbalances which make the difference between regions that can have an adverse influence (backwash effects) dominating the beneficial influence (spread effects) on regional growth. One indicator that is quite representative to measure the level of development inequality between regions is the Williamson index. Inequality in the former Kedu residency continues to increase in each year and further widens the gap between the regions. In this study, the variables of private investment, labor force, and Special Allocation Fund (DAK) are used in 6 districts/cities of the former Kedu residency of Central Java Province in 2007-2016. By using regression analysis method or panel, the results showed: 1) private investment has no effect on economic development inequality, 2) work force has a positive effect on development inequality, and 3) DAK has no effect on imbalance of economic development in the districts/cities of the former Kedu residency in Central Java Province in 2007-2016.Keyword: Regional Inequality, Private Investment, DAK, Labor Force, Williamson Index.